Personality Profile - Karmacharya, Janak Lal (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Not Available. HYDRO Nepal Journal of Water Energy and EnvironmentVolume- 18, 2016, JanuaryPage -61 to 62